Chromosome studies of some species of Vernonanthura and Vernonia (Asteraceae, Vernonieae) - Vega, Alvaro Jose (2012)
The chromosome numbers of 18 populations belonging to 10 species of Vernonanthura H. Rob. and one species of Vernonia Schreb. (Vernonieae, Asteraceae) from South America were determined. First chromosome counts are presented for three taxa: Vernonanthura lucida (Less.) H. Rob. (n = 17, 2n = 34), V. oligactoides (Less.) H. Rob. (n = 17, 2n = 34) and V. pseudolinearifolia (Hieron.) Vega et Dematt. (2n = 34). In addition, a new cytotype is reported for Vernonia echioides Less. (2n = 34), a widely distributed species in which only tetraploid populations (n = 34, 2n = 68) were recorded to date. The chromosome numbers found in Vernonanthura amplexicaulis (R.E.Fr.) H. Rob. (2n = 34), V. chamaedrys (n = 17, 2n = 34), V. ferruginea (Less.) H. Rob. (2n = 34), V. loretensis (Hieron.) H. Rob. (2n = 34), V. nudiflora (Less.) H. Rob. (2n = 34), V. squamulosa (Hook. et Arn.) H. Rob. (n = 17, 2n = 34), V. tweediana (Baker) H. Rob. (2n = 34) and Vernonia echioides (n = 34) are in agreement with previous records for these species. All the species of Vernonanthura and Vernonia analyzed here showed basic number x2 = 17 and almost all them were diploid with 2n = 34. The single exception was Vernonia echioides which showed diploid (2n = 34) and tetraploid (2n = 68) populations.